Analysis of Employee Performance In the Implementation of District and Sub-District Monograph Recording at the Medan Helvetia Sub-District Office - Rio Rahmad Alam Siregar; Nina Siti Salmaniah Siregar; Syafruddin Ritonga (International Journal of Integrated Science and Technology, 2024)
This research aims to analyze the performance of employees in carrying out the recording of district and subdistrict monographs at the Medan Helvetia District Office. District and subdistrict monographs play a crucial role as fundamental data in regional planning and development. Employee performance in the implementation of monograph recording is a critical factor to ensure the integrity, accuracy, and availability of the required data. This research uses a descriptive-analytical approach by collecting data through observation, interviews, and analysis of related documents. The research respondents are employees directly involved in the implementation of monograph recording at the Medan Helvetia District Office. The results of the study indicate that the performance of employees in the implementation of monograph recording still faces several challenges. Factors such as a lack of training, excessive workload, and limited resources are major obstacles. In addition, the suboptimal reporting and monitoring system also has a negative impact on the quality of recording. The recommendations of this research include expanding training for employees, reviewing task allocation to reduce workload, improving information technology infrastructure, and optimizing the reporting system. With the implementation of these recommendations, it is expected that the performance of employees in the implementation of monograph recording can be improved, resulting in more reliable data to support decision-making at the district and subdistrict levels.